Can linguistics and semiotics conceive man without language? - Fadda, Emanuele (Sign Systems Studies, 2022)
Saussure’s refusal to adopt a biological perspective in linguistics and to consider the problem of the origin of language does not imply a struggle against the natural and biological aspects of language. Rather, it derives from the awareness that it is impossible to look at language “from the outside” if one wants (as Saussure considers obligatory for the linguist) to drop into the perspective of the speaking subjects. This tendency to consider the nature of language “from within” has a strong philosophical importance.